Reaching unreachables: Obstacles and successes of microbial cultivation and their reasons - Kapinusova, Gabriela; Lopez Marin, Marco A.; Uhlik, Ondrej (Frontiers in Microbiology, 2023)
In terms of the number and diversity of living units, the prokaryotic empire is the most represented form of life on Earth, and yet it is still to a significant degree shrouded in darkness. This microbial ˈdark matterˈ hides a great deal of potential in terms of phylogenetically or metabolically diverse microorganisms, and thus it is important to acquire them in pure culture. However, do we know what microorganisms really need for their growth, and what the obstacles are to the cultivation of previously unidentified taxa? Here we review common and sometimes unexpected requirements of environmental microorganisms, especially soil-harbored bacteria, needed for their replication and cultivation. These requirements include resuscitation stimuli, physical and chemical factors aiding cultivation, growth factors, and co-cultivation in a laboratory and natural microbial neighborhood.